Fool's quest - Hobb, Robin (New York : Del Rey, 2016)
"After nearly killing his oldest friend, the Fool, and finding his daughter stolen away by those who were once targeting the Fool, FitzChivalry Farseer is out for blood. And who better to wreak havoc than a highly trained and deadly former royal assassin? Fitz might have let his skills go fallow over his years of peace, but such things, once learned, are not so easily forgotten. And nothing is more dangerous than a man who has nothing left to lose."
Includes excerpt from Assassin's Fate.
Keywords: Assassins -- Fiction; Magic -- Fiction; Revenge -- Fiction; Fantasy fiction